2006
DOI: 10.1353/sof.2006.0101
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Spatial Variation in Tolerance: The Effects of Education and Religion

Abstract: Prior research has shown that individuals living in Southern areas express significantly less tolerant attitudes than the rest of the nation, while individuals residing in urban areas express significantly more tolerant attitudes than their rural peers. We seek to explain these generally unspecified Southern and urban effects by identifying demographic contextual factors that affect individuals' tolerance levels. Using 1976 General Social Survey and 1990 Census data, we find that net of individual factors, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
65
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 36 publications
11
65
0
Order By: Relevance
“…According to Kosciw et al's (2009) research, which included a nationally representative sample of 5,420 sexual minority high school students (mean age, 15.9) in rural and impoverished communities with low adult educational attainment experience hostile school environment where they are victimized by peers. Consistent with previous findings (e.g., Moore and Ovadia 2006;Ohlander et al 2005), the study also found that LGBT students residing in communities with high proportion of college-educated residents are victimized less frequently in school.…”
Section: Microsystem Levelsupporting
confidence: 91%
“…According to Kosciw et al's (2009) research, which included a nationally representative sample of 5,420 sexual minority high school students (mean age, 15.9) in rural and impoverished communities with low adult educational attainment experience hostile school environment where they are victimized by peers. Consistent with previous findings (e.g., Moore and Ovadia 2006;Ohlander et al 2005), the study also found that LGBT students residing in communities with high proportion of college-educated residents are victimized less frequently in school.…”
Section: Microsystem Levelsupporting
confidence: 91%
“…I control for age because it has been shown in previous research to correlate positively with prejudice (Case, Greely, and Fuchs 1989). Existing literature likewise suggests that education has a negative effect on xenophobia (Case, Greely, and Fuchs 1989;Hjerm 2005;Moore and Ovadia 2006). Lipset (1959) postulated that the working class was especially at risk of harboring authoritarian and exclusionary attitudes, and his theory has been borne out by subsequent research (Andersen and Bjørklund 1990;Kitschelt and McGann 1997;Oesch 2008a).…”
Section: Methodsmentioning
confidence: 98%
“…To the extent that these insights have been integrated into research on intergroup relations, the cases examined have been confined mostly to the United States. These investigations found some evidence that residing in a city exerts a positive effect on tolerance for out-groups (Tuch 1987;Wilson 1991), although some researchers argue that the urban effect is either in decline (Abrahamson and Carter 1986) or disappears entirely once controls for education are included (Moore and Ovadia 2006). I aim to extend on this body of research by posing a similar question in a non-American context.…”
Section: Xenophobia and The Citymentioning
confidence: 99%
“…Although there are indications that the southern distinctiveness in religion may be declining (Schwadel 2010), our data reveal variation in rates of cohabitation that suggests a connection between Southern context, conservative religious behavior, and normative constraints against an unconventional lifestyle. In a recent study of Southern religiosity and intolerance, Moore and Ovadia (2006) argue that the impact of Southern conservative religiosity can be both direct and indirect. The impact is direct, they argue, when religious adherents are explicitly encouraged by pastors and fellow congregants to embody non-tolerant values.…”
Section: Regional Considerationsmentioning
confidence: 99%